Intermittent horizontal saccade failure ('ocular motor apraxia') in children. Issue 2 (February 1996) - Harris, C M; Shawkat, F; Russell-Eggitt, I; Wilson, J; Taylor, D
Abstract : BACKGROUND: Ocular motor apraxia (OMA) in childhood is a poorly understood condition involving a failure of horizontal saccades. OMA is thought to be rare but the literature indicates wide clinical associations. OMA is often identified by abnormal head movements, but failure of reflexive quick phases has been reported in all but a few patients. The extent of this oculomotor disorder was examined in a large group of children with diverse clinical backgrounds. METHODS: The degree of quick phase failure during horizontal vestibular and optokinetic nystagmus was measured using DC electro-oculography and video in 74 affected children, aged 17 days to 14 years. RESULTS: All children showed an intermittent failure of nystagmic quick phases, except for total failure in one case. Other visuomotor abnormalities were common including saccadic hypometria (85%), low gain smooth pursuit (70%), neurological nystagmus (28%), strabismus (22%), and vertical abnormalities (11%). Non-ocular abnormalities were common including infantile hypotonia (61%), motor delay (77%), and speech delay (87%). There was a wide range of clinical associations including agenesis of the corpus callosum, Joubert syndrome, Dandy-Walker malformation, microcephaly, hydrocephalus, vermis hypoplasia, porencephalic cyst, megalocephaly, Krabbe leucodystrophy, Pelizaeus Merzbacher disease, infantile Gaucher disease, GM1 gangliosidosis, infantile Refsum's disease, propionic acidaemia, ataxia telangiectasia, Bardet-Biedl syndrome, vermis astrocytoma, vermis cyst, carotid fibromuscular hypoplasia, Cornelia de Lange syndrome, and microphthalmos. Perinatal and postnatal problems were found in 15% including perinatal hypoxia, meningitis, periventricular leucomalacia, athetoid cerebral palsy, perinatal septicaemia and anaemia, herpes encephalitis, and epilepsy. Only 27% were idiopathic. CONCLUSION: Quick phase failure is a constant feature of OMA, whereas abnormal head movements were detected in only about half, depending on the underlying diagnosis. This oculomotor sign is better described as an intermittent saccade failure rather than as a true apraxia. It indicates central nervous system involvement, has wide clinical associations, but it is not a diagnosis.